Method for preparing positive electrode, the positive electrode prepared thereby, and secondary battery comprising the positive electrode

KR103020654B1Active Publication Date: 2026-09-16LG ENERGY SOLUTION LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020240063873
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-05-23
Filing Date
2024-05-16
Publication Date
2026-09-16
Estimated Expiration
2044-05-16

Smart Images

  • Figure 112024052872880-PAT00001_ABST
    Figure 112024052872880-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing an electrode, wherein the manufacturing method comprises: a step P1 of forming an electrode structure by placing a transfer laminate comprising a lithium metal layer having lithium buffer layers formed on both sides onto a pre-electrode active material layer so that the lithium buffer layer and the pre-electrode active material layer come into contact; a step P2 of rolling the electrode structure; and a step P3 of aging the rolled electrode structure in a nitrogen atmosphere, wherein the nitrogen atmosphere is an atmosphere containing 80 volume% or more of nitrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing an electrode, an electrode manufactured thereby, and a lithium secondary battery comprising said electrode. Background Technology

[0003] Due to the rapid increase in the use of fossil fuels, there is a growing demand for alternative or clean energy. As part of this effort, the fields of power generation and energy storage utilizing electrochemical reactions are the most actively researched.

[0004] Currently, a representative example of an electrochemical device utilizing such electrochemical energy is the secondary battery, and its scope of application is increasingly expanding. Recently, with the technological development and growing demand for portable devices such as portable computers, mobile phones, and cameras, the demand for secondary batteries as an energy source has been rapidly increasing. Among these secondary batteries, much research has been conducted on lithium secondary batteries, which have high energy density—that is, high capacity—and have been commercialized and are widely used.

[0005] Generally, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and extracts lithium ions from the positive electrode, and silicon-based active material particles with a high discharge capacity may be used as the negative electrode active material. The silicon-based active material particles are Si or SiO X (0 <X<2) 등에 해당될 수 있다. 실리콘계 활물질 입자는 이론 용량이 크고 가격이 저렴한 장점이 있다. 다만, 실리콘계 활물질 입자는 전지 구동 시, 부피 변화가 지나치게 크므로, 전지의 사이클이 진행될수록 전지의 수명이 급격히 줄어드는 단점이 있다.

[0006] Therefore, to minimize volume changes of silicon-based active material particles, a method exists to utilize only a portion of the total capacity of the silicon-based active material particles. To this end, a so-called pre-lithiation process is used, in which lithium ions are pre-inserted into the anode containing the silicon-based active material particles. Specifically, by inserting lithium ions into the anode through methods such as transferring lithium metal to the anode, the lithium ions react at the irreversible sites of the anode, thereby reducing the total capacity of the anode to a reversible capacity level. Consequently, since the amount of lithium ions inserted during battery operation can be appropriately reduced to the level required for battery operation, volume changes of the silicon-based active material particles can be minimized.

[0007] However, during the process of pre-lithiation by placing lithium metal on the surface of the cathode, excessive heat is generated due to the alloy reaction between lithium and silicon, and the possibility of ignition due to the reaction between lithium and moisture also increases. In addition, during the process of notching and punching the cathode, the possibility of ignition can increase further due to the increased reaction surface area between lithium and silicon-based active material, and there is a serious safety issue that there is also a possibility of ignition caused by silicon-based active material particles that have undergone pre-lithiation.

[0008] Therefore, a new technology is required that can improve battery life by pre-inserting lithium ions into the negative electrode before battery operation, while suppressing excessive heat generation and the possibility of ignition. The problem to be solved

[0010] The problem that the present invention aims to solve is to provide a method for manufacturing an electrode that, when transferring lithium metal to an electrode for pre-lithiation, utilizes a lithium metal layer with lithium buffer layers formed on both sides, thereby preventing the formation of an inactive layer on the surface of the lithium metal layer due to side reactions of highly reactive lithium, while allowing the pre-lithiation reaction to be performed in a stable atmosphere, and when activated after pre-lithiation, the lithium buffer layer decomposes without affecting the electrode thickness, thereby preventing a decrease in energy density, and utilizes the decomposed lithium as an additional lithium source to maximize the pre-lithiation effect.

[0011] Another problem that the present invention aims to solve is to provide a secondary battery comprising an electrode manufactured by the above manufacturing method, wherein lifespan characteristics are improved by controlling the available area of ​​the negative electrode, and the inherent characteristics of the negative electrode active material can be realized without disadvantage. means of solving the problem

[0013] To solve the above problem, in one aspect of the present invention, a method for manufacturing an electrode is provided, comprising: a step P1 of forming an electrode structure by placing a transfer laminate comprising a lithium metal layer having lithium buffer layers formed on both sides on a pre-electrode active material layer so that the lithium buffer layer and the pre-electrode active material layer come into contact; a step P2 of rolling the electrode structure; and a step P3 of aging the rolled electrode structure in a nitrogen atmosphere, wherein the nitrogen atmosphere is an atmosphere containing 80 volume% or more of nitrogen.

[0014] In order to solve the above problem, in another aspect of the present invention, an electrode is provided comprising: a current collector; an electrode active material layer disposed on the current collector; and a lithium buffer layer disposed on the electrode active material layer, wherein the lithium buffer layer comprises one or more of lithium carbonate, lithium oxide, and lithium hydroxide, and does not contain lithium nitride.

[0015] In order to solve the above problem, in another aspect of the present invention, a lithium secondary battery is provided comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode as described above, wherein the positive electrode or the negative electrode is the electrode described above. Effects of the invention

[0017] The method for manufacturing an electrode according to the present invention utilizes a lithium metal layer with a lithium buffer layer formed on both sides, thereby preventing the formation of an inactive layer on the surface of the lithium metal layer due to side reactions of highly reactive lithium, which can resolve the problem of increased resistance. Furthermore, upon activation after pre-lithiation, the lithium buffer layer decomposes without affecting the electrode thickness, thus preventing a decrease in energy density. Additionally, the lithium buffer layer can be utilized as an additional lithium source through decomposition, thereby maximizing the pre-lithiation effect and reducing process risks associated with direct contact of lithium metal with the anode.

[0018] In addition, the lithium secondary battery according to the present invention includes an electrode manufactured by the above-described manufacturing method, thereby increasing the usable area of ​​the negative electrode and consequently increasing the capacity. In particular, when using a silicon-based negative electrode active material, only a portion of the usable area can be utilized without lithium loss in the positive electrode due to pre-lithiated lithium, and thus, there is an advantage in that lifespan characteristics can be improved by minimizing volume change. Brief explanation of the drawing

[0020] FIG. 1 is a schematic diagram showing step P1 in a method for manufacturing an electrode according to one embodiment of the present invention. FIG. 2 is a schematic diagram showing step P1 using an electric laminate including a polymer layer in a method for manufacturing an electrode according to one embodiment of the present invention. FIG. 3 is a schematic diagram showing step P2 in a method for manufacturing an electrode according to one embodiment of the present invention. FIG. 4 is a schematic diagram showing step P2' in a method for manufacturing an electrode according to one embodiment of the present invention. FIG. 5 is a photograph of the electrode surface of Example 1-1 taken after performing pre-lithiation according to one embodiment of the present invention. Figure 6 is a photograph of the electrode surface of Comparative Example 1-1 taken after performing pre-lithiation. Figure 7 is a photograph of the electrode surface of Comparative Examples 1-4 taken after performing pre-lithiation. Specific details for implementing the invention

[0021] Hereinafter, the present invention will be described in more detail to aid in understanding the invention.

[0022] Terms and words used in this specification and claims shall not be interpreted as being limited to their ordinary or dictionary meanings, but shall be interpreted in a meaning and concept consistent with the technical spirit of the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0023] The terms used herein are merely for describing exemplary embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise.

[0024] In this specification, terms such as “comprising,” “comprising,” or “having” are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should not be understood as precluding the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0025] D in this specification 50 In the particle size distribution curve of silver particles, it can be defined as the particle size corresponding to 50% of the cumulative volume. The above D 50For example, it can be measured using the laser diffraction method. The laser diffraction method generally enables the measurement of particle sizes ranging from the submicron range to several millimeters, and can obtain results with high reproducibility and high resolution.

[0027] Method for manufacturing an electrode

[0028] A method for manufacturing an electrode according to the present invention provides a method for manufacturing an electrode comprising: a step P1 of forming an electrode structure by placing a transfer laminate comprising a lithium metal layer having lithium buffer layers formed on both sides onto a pre-electrode active material layer so that the lithium buffer layer and the pre-electrode active material layer come into contact; a step P2 of rolling the electrode structure; and a step P3 of aging the rolled electrode structure in a nitrogen atmosphere.

[0030] According to one embodiment of the present invention, the step P1 of the method for manufacturing the electrode comprises placing a transfer laminate including a lithium metal layer having lithium buffer layers formed on both sides onto a preliminary electrode active material layer formed on a current collector to form an electrode structure such that the lithium buffer layer and the preliminary electrode active material layer come into contact.

[0031] Referring to FIG. 1, the transfer laminate (300) includes a lithium metal layer (320), and a lithium buffer layer (321) is formed on both sides of the lithium metal layer. Additionally, the transfer laminate (300) may preferably further include a substrate film (310), in which case it may include a substrate film (310) and a lithium metal layer (320) located on the substrate film (310), and may have a structure in which a lithium buffer layer (321) is formed on both sides of the lithium metal layer. The substrate film (310) may be used without limitation as long as it is a material capable of withstanding high temperature conditions that occur during the process of depositing the lithium metal layer (320) on the substrate film (310). Specifically, the above-described film may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), poly(methylmethacrylate), PMMA, polypropylene, polyethylene, and polycarbonate.

[0032] According to one embodiment of the present invention, the lithium metal layer serves to supply lithium ions to the pre-electrode active material layer. Specifically, the pre-electrode active material layer may be located between the electrode current collector and the lithium buffer layer on the lithium metal layer.

[0033] The lithium metal layer comprises solid lithium metal, and specifically, the lithium metal layer may be composed of solid lithium metal. The lithium metal layer may be inserted into the electrode active material layer through solid diffusion of lithium metal via a series of processes such as transfer, rolling, and aging. Accordingly, the lithium metal layer may not exist after activation, and may exist in a state where its thickness is extremely thin.

[0034] Meanwhile, the lithium metal layer may be composed of solid lithium metal, and lithium metal is a highly reactive metal that can react with oxygen (O2), nitrogen (N2), or water vapor (H2O) even in an air atmosphere. Due to this reaction, loss may occur in the lithium metal or an inactive layer, such as lithium nitride or lithium oxide, may be formed on the surface. The presence of such an inactive layer can act as a resistor and cause problems that degrade the output characteristics of the secondary battery. Since a layer that does not perform a special function exists on the electrode, the impact may not be significant at the cell level, but a decrease in energy density may be a problem at the module or pack level.

[0035] To solve these problems, according to one embodiment of the present invention, the lithium metal layer is provided with lithium buffer layers formed on both sides, so that even when the substrate film is removed from the electrode structure, the lithium metal layer is not exposed to the outside and the lithium buffer layer exists on the top layer. The lithium buffer layer may include lithium carbonate (Li2CO3), and the main component may be lithium carbonate. It may further include one or more of lithium oxide (LiO, Li2O) and lithium hydroxide (LiOH) as by-products, but is characterized by not including at least lithium nitride (Li3N). Specifically, the lithium buffer layer may contain 80 weight% or more of lithium carbonate, preferably 85 weight% or more, more preferably 90 weight% or more, or 95 weight% or more. If the lithium carbonate content is less than the above amount, the amount of other lithium compounds increases relatively, and in this case, it may be difficult to expect the aforementioned effect.

[0036] According to one embodiment of the present invention, a lithium buffer layer formed between the lithium metal layer and the substrate film prevents the lithium metal layer from being exposed to air before or after pre-lithiation or during the transfer process, thereby significantly reducing the possibility of side reactions, and thereby preventing an inactive layer, the main component of which is lithium nitride and / or lithium oxide, from being formed on the surface of the lithium metal layer.

[0038] Furthermore, lithium carbonate, which is the main component of the lithium buffer layer, can be decomposed during the activation process after pre-lithiation, and the lithium generated during this decomposition can be used as an additional lithium source, which has the advantage of contributing to the improvement of battery capacity and lifespan. Moreover, since there is no transfer laminate used for pre-lithiation remaining on the electrode after the activation process, it can completely avoid affecting the electrode thickness, which allows for the expectation of improved energy density at the module or pack level.

[0039] Meanwhile, the lithium buffer layer may include lithium oxide and / or lithium hydroxide, which may be compounds that inevitably occur when forming a lithium buffer layer on a lithium metal layer.

[0040] In addition, the lithium nitride is characterized by not being included in the lithium buffer layer. Lithium nitride has higher stability than other lithium compounds and does not decompose easily even after tens or hundreds of cycles. It may also be a compound that causes problems, such as significant lithium loss due to the high proportion of lithium it fixes, and subsequently acting as a resistor to degrade output characteristics. Accordingly, the lithium buffer layer according to one embodiment of the present invention may not include lithium nitride, and this can be appropriately controlled through surface treatment of the lithium metal layer when manufacturing the transfer laminate.

[0042] According to one embodiment of the present invention, the transfer laminate can be manufactured by a method comprising the step (S1) of surface treating both sides of a lithium metal layer to form a lithium buffer layer. Additionally, if the transfer laminate includes a substrate film, it can be manufactured by a method further comprising the step (S2) of placing the substrate film on one of the lithium buffer layers.

[0043] The method of surface treating both sides of the above lithium metal layer may be a method of creating a mixed gas atmosphere of CO2 and Ar at the beginning of deposition to induce a reaction with lithium when forming a film by depositing lithium, and then creating the mixed gas atmosphere again after the deposition of lithium to a desired thickness is completed; alternatively, a lithium buffer layer mainly composed of lithium carbonate may be formed simultaneously on both sides by introducing the lithium metal film into a vacuum chamber and creating the mixed gas atmosphere. The mixed gas may be a mixture of CO2 and Ar in a volume ratio of about 3:97 to 40:60, preferably a volume ratio of 5:95 to 30:70, and more preferably 5:95 to 20:80.

[0045] According to one embodiment of the present invention, the thickness of the lithium buffer layer may be 50 nm or less, and this can be controlled to an appropriate level by adjusting the conditions of the method. When the thickness of the lithium buffer layer is 50 nm or less, it can act as a lithium source at a level that can be decomposed through activation, and side reactions of the lithium metal layer can be effectively prevented.

[0046] According to one embodiment of the present invention, in the transfer laminate, the thickness of the lithium metal layer may be 1 μm to 10 μm, specifically 3 μm to 9 μm, and more specifically 4 μm to 6.5 μm. When the above range is satisfied, the degree of breakage of positive active material particles on the surface of the positive electrode may be reduced, and an explosive reaction at the negative electrode may be prevented in advance, so that the initial capacity reduction of the battery may be suppressed.

[0047] According to one embodiment of the present invention, the loading amount of the lithium metal layer (unit: mAh / cm²) 2 ) is the loading amount of the above-mentioned pre-electrode active material layer (unit: mAh / cm² 2 The amount may be 4% to 40%, specifically 12% to 35%, and more specifically 20% to 30%. When the above range is satisfied, the generation of byproducts is low, and lithium can be easily inserted into the electrode active material, so the target lithium insertion capacity can be easily achieved.

[0049] According to one embodiment of the present invention, in step P1, with reference to FIG. 1, the preliminary electrode active material layer (120') is located on the electrode current collector (110), and the transfer laminate (300) is disposed on the preliminary electrode active material layer (120'), so that the lithium buffer layer (321) and the preliminary electrode active material layer come into contact with each other, so that an electrode structure (400) can be formed.

[0051] Meanwhile, referring to FIG. 2, the transfer laminate (300) according to one embodiment of the present invention may further include a polymer layer (330). The polymer layer (330) may be located on the lithium buffer layer (321). During the manufacture of the electrode, the polymer layer may serve to effectively peel off the lithium metal layer from the transfer laminate so that the lithium metal layer can be easily transferred to the electrode active material layer. That is, the polymer layer may be detached from the transfer laminate together with the lithium metal layer and located on the electrode active material layer. The polymer layer may exist in contact with the electrode active material layer, or, if the lithium metal layer is not entirely transferred to the electrode active material layer, a lithium metal layer may exist between the polymer layer and the electrode active material layer.

[0052] The polymer layer may be at least one selected from the group consisting of polyethylene terephthalate (PET), polyimide (PI), poly(methylmethacrylate) (PMMA), polypropylene, polyethylene, and polycarbonate. Accordingly, in a secondary battery including the electrode, the polymer layer may be dissolved in the electrolyte contained in the secondary battery, thereby preventing an increase in the resistance of the battery. In particular, the polymer layer may include PMMA, in which case the above-described effect may be further improved.

[0053] The thickness of the polymer layer may be 0.1 μm to 10 μm, specifically 0.5 μm to 5 μm, and more specifically 1 μm to 2.5 μm. When the above range is satisfied, the lithium metal layer can be easily transferred to the electrode active material layer, and the reverse transfer phenomenon in which the electrode active material layer is transferred to the transfer laminate can be prevented.

[0055] According to one embodiment of the present invention, step P2 of the method for manufacturing the electrode is a step of rolling the electrode structure.

[0056] Referring to FIG. 3, in step P2, the manufactured electrode structure (400) can be rolled. The rolling can be performed using a roll press method. Specifically, pressure can be applied in the vertical direction to the electrode structure (400) passing through the space using two rolls (R) spaced apart with a predetermined space in the vertical direction, and the pressure can be a linear pressure. Through the rolling process, the lithium metal layer included in the transfer laminate can be fixed as a layer within the positive electrode structure, and at least some of the lithium can begin to be inserted into the pre-electrode active material layer.

[0057] The pressure applied to the electrode structure during the above rolling may be 10 kgf / cm to 90 kgf / cm, specifically 15 kgf / cm to 80 kgf / cm, and more specifically 20 kgf / cm to 40 kgf / cm.

[0058] When the above rolling pressure is applied within the above range, the lithium metal layer can be effectively transferred. Accordingly, it is possible to achieve an effect that simultaneously satisfies improved lifespan and capacity characteristics.

[0060] According to one embodiment of the present invention, the method for manufacturing the electrode may further include the step of removing the substrate film from the electrode structure after rolling in step P2, when the transfer laminate (300) includes a substrate film (310).

[0061] Referring to FIG. 4, in step P2', the electrode (100) can be manufactured by removing the substrate film (310) from the electrode structure after rolling performed in step P2. When the polymer layer (330) is located on the lithium buffer layer (321), the polymer layer (330) is located between the substrate film (310) and the lithium buffer layer (321), thereby allowing the substrate film (310) to be removed more easily.

[0063] According to one embodiment of the present invention, the method for manufacturing the electrode comprises a step P3 of aging the rolled electrode structure in a nitrogen atmosphere.

[0064] The above aging may be a step of resting (leaving) for 1 minute to 600 minutes, specifically for 1 minute to 30 minutes, under a nitrogen atmosphere. At this time, the nitrogen atmosphere may have a nitrogen concentration of 80 volume% or more, or 85 volume% or more, and preferably 90 volume% or more. The above aging may be performed at a temperature of 15°C to 40°C, preferably 17°C or more, or 20°C or more, preferably 35°C or less, more preferably 30°C or less, or 28°C or less. The above aging conditions allow for the expectation of stability, as the explosive pre-lithiation reaction is effectively controlled by applying a nitrogen atmosphere, thereby significantly reducing the risk of fire and allowing the reaction to proceed stably. Furthermore, even when a nitrogen atmosphere is applied, the lithium buffer layer prevents the formation of lithium nitride on the surface of the lithium metal, thus preventing problems such as increased resistance caused by the formation of lithium nitride.

[0066] electrode

[0067] The electrode according to the present invention comprises a current collector; an electrode active material layer disposed on the current collector; and a lithium buffer layer disposed on the electrode active material layer, wherein the lithium buffer layer comprises one or more of lithium carbonate, lithium oxide, and lithium hydroxide, and is characterized by not containing lithium nitride.

[0068] Specifically, the electrode may be derived from an electrode structure comprising: a transfer laminate including a lithium metal layer having a lithium buffer layer formed on both sides; and a pre-electrode including a current collector and a pre-electrode active material layer disposed on the current collector, wherein the lithium buffer layer of the transfer laminate and the pre-electrode active material layer of the pre-electrode are disposed in contact.

[0070] According to one embodiment of the present invention, the electrode may be a positive electrode, and the positive electrode comprises a positive electrode active material layer. The positive electrode active material layer may constitute the positive electrode itself, but the positive electrode active material layer may be located on a positive electrode current collector, and the positive electrode active material layer may be located on one or both sides of the positive electrode current collector.

[0071] According to one embodiment of the present invention, the positive current collector is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the positive current collector may typically have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesion of the positive active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0073] According to one embodiment of the present invention, the positive active material layer comprises a positive active material, and the positive active material is a material capable of causing an electrochemical reaction and may be a lithium transition metal oxide. For example, the positive active material may be a layered compound such as lithium cobalt oxide or lithium nickel oxide substituted with one or more transition metals; lithium manganese oxide substituted with one or more transition metals; Li[Ni 1-y M 1 y ]O2(here, M 1 A lithium nickel-based oxide represented by , where is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B, Cr, Zn, and Ga, and 0.01≤y≤0.7; Li 1+z [Ni b Mn c Co 1-(b+c+d) M 2 d ]O (2-e) A e (Here, M 2 A lithium nickel cobalt manganese composite oxide represented by , where is at least one selected from the group consisting of Al, Mg, Cr, Ti, Si, and Y, A is at least one selected from the group consisting of F, P, and Cl, and -0.5≤z≤0.5, 0.1≤b≤0.8, 0.1≤c≤0.8, 0≤d≤0.2, 0≤e≤0.2, b+c+d<1; Li 1+x [M 3 1-q M 4 q ]PO 4-r X r (Here, M 3 is at least one selected from the group consisting of Fe, Mn, Co, and Ni, and M 4It may include at least one selected from the group consisting of olivine-based lithium metal phosphates, represented as (where is at least one selected from the group consisting of Al, Mg, and Ti, X is at least one selected from the group consisting of F, S, and N, and -0.5≤x≤0.5, 0≤q≤0.5, 0≤r≤0.1).

[0074] Specifically, the positive electrode active material may be composed of a lithium nickel-based oxide, a lithium nickel cobalt manganese composite oxide, an olivine-based lithium metal phosphate, or a combination thereof, and the positive electrode active material layer may be formed as a single layer or as separate layers by combining these.

[0075] According to one embodiment of the present invention, more specifically, the positive active material may include a compound of the following chemical formula 1, and more specifically, may be a compound of the following chemical formula 1.

[0076] [Chemical Formula 1]

[0077] Li 1+x [Ni a Co b Mn c M 1 (1-a-b-c) ]O (2-d) A d

[0078] In the above chemical formula 1,

[0079] M 1 can be at least one selected from the group consisting of Al, Mg, Cr, Ti, Si, and Y, and specifically can be Al.

[0080] A is at least one selected from the group consisting of F, P, and Cl, and specifically can be F.

[0081] The above x can satisfy -0.5≤x≤0.5, specifically -0.3≤x≤0.3.

[0082] The above a can satisfy 0.6≤a<1, specifically 0.7≤a≤0.9.

[0083] The above b can satisfy 0.03≤b≤0.1, specifically 0.05≤b≤0.1.

[0084] The above c can satisfy 0.03≤c≤0.1, specifically 0.05≤c≤0.1.

[0085] The above d can satisfy 0≤d≤0.1, specifically 0≤d≤0.05.

[0086] The above a, b, and c are 0 <a+b+c≤1, 구체적으로 a+b+c=1를 만족한다.

[0087] The compound of Chemical Formula 1 above may be in the form of particles.

[0088] The compound of Chemical Formula 1 above may be in the form of secondary particles in which a plurality of primary particles are bonded together. Specifically, the compound of Chemical Formula 1 above may be in the form of secondary particles in which 10 or more primary particles are bonded together. Accordingly, there is an effect that lithium can be uniformly inserted into and extracted from the interior of the positive electrode active material.

[0089] D of the compound of Chemical Formula 1 above 50 The value may be 5㎛ to 15㎛, specifically 7㎛ to 12㎛, and more specifically 9㎛ to 10㎛. The above D 50 The D of the secondary particle 50 It may be possible. When the above range is satisfied, the dispersion of the anode slurry is easy, and a uniform coating of the anode active material layer is possible.

[0090] The above positive active material may be included in the above positive active material layer in an amount of 90% to 99% by weight, specifically 92% to 98% by weight, and more specifically 95% to 98% by weight.

[0091] According to one embodiment of the present invention, the positive active material layer may further include a positive binder. The positive binder serves to improve adhesion between positive active material particles and adhesion between the positive active material and the positive current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.

[0092] The anode binder may be included in the anode active material layer in an amount of 0.5% to 5.0% by weight, specifically 1.0% to 2.5% by weight, and more specifically 1.0% to 2.0% by weight.

[0093] According to one embodiment of the present invention, the positive active material layer may further include a positive conductive material. The positive conductive material is used to impart conductivity to the electrode, and in the battery being constructed, it may be used without special limitations as long as it has electronic conductivity without causing chemical changes. Specific examples include graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, or silver; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and one of these alone or a mixture of two or more may be used.

[0094] The above-mentioned positive conductive material may be included in the above-mentioned positive active material layer in an amount of 0.5% to 30.0% by weight, specifically in an amount of 0.5% to 10.0% by weight, and more specifically in an amount of 1.0% to 4.0% by weight.

[0095] According to one embodiment of the present invention, in the anode, the porosity of the anode active material layer may be 10% to 40%, specifically 15% to 35%, and more specifically 25% to 30%. In this case, no additional change in thickness may occur during rolling.

[0097] According to one embodiment of the present invention, the electrode may be a cathode, and the cathode may include a cathode active material layer, and the cathode active material layer may include a cathode active material, and the cathode active material may be a silicon-based cathode active material, a carbon-based cathode active material, or a combination thereof.

[0098] According to one embodiment of the present invention, the negative electrode active material may include a silicon-based negative electrode active material. The silicon-based negative electrode active material comprises Si and SiO x (0 <X<2) 중 적어도 어느 하나를 포함할 수 있다.

[0099] The above Si is a silicon particle. It may be a silicon particle called so-called Pure Silicon (a particle composed of silicon). The above silicon particle can effectively improve the capacitance of the cathode. The above SiO x (0 <X<2)는 Si 및 SiO2가 포함된 형태일 수 있으며, 상기 Si는 상(phase)을 이루고 있을 수도 있다. 즉, 상기 X는 상기 SiO x (0 <X<2) 내에 포함된 Si에 대한 O의 개수비에 해당한다. 상기 실리콘계 복합 입자가 상기 SiO x (0 <X<2)를 포함하는 경우, 이차 전지의 방전 용량이 개선될 수 있다.

[0100] According to one embodiment of the present invention, the silicon-based negative electrode active material has a problem of very poor lifespan characteristics due to severe volume changes during battery operation. However, when combined with a positive electrode according to the method of manufacturing an electrode according to the present invention, excess lithium ions other than the lithium in the positive electrode active material that determines capacity are moved from the pre-lithiated positive electrode to the silicon-based negative electrode active material upon activation and react with the silicon-based negative electrode active material in advance to form an irreversible phase, thereby reducing the available area. Consequently, the volume change during battery operation is not severe, so the lifespan can be significantly improved, and the high capacity characteristics inherent to the silicon-based negative electrode active material can be fully expressed. Furthermore, even when the manufacturing method according to one embodiment of the present invention is applied to the silicon-based negative electrode active material itself, it is possible to control the pre-lithiation reaction through a lithium buffer layer while obtaining the effects described above, thereby reducing the risk associated with the conventional alloy reaction between lithium and silicon.

[0102] According to one embodiment of the present invention, the negative electrode active material may further include a carbon-based negative electrode active material. The carbon-based negative electrode active material may include at least one selected from the group consisting of artificial graphite, natural graphite, and graphitized mesocarbon micro beads.

[0103] According to one embodiment of the present invention, the negative electrode active material layer may further include a negative electrode binder. The above-mentioned cathode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and materials in which the hydrogens thereof are substituted with Li, Na, or Ca, etc., and may also include various copolymers thereof.

[0104] According to one embodiment of the present invention, the negative electrode active material layer may further include a negative electrode conductive material. The negative electrode conductive material is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, Farnes black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives may be used.

[0106] In one embodiment of the present invention, the electrode has a lithium metal layer disposed on the electrode via a transfer method, and lithium from the lithium metal layer is inserted into the electrode active material layer by solid-state diffusion through rolling. This lithium can serve to reduce the usable area of ​​the negative electrode.

[0107] Therefore, since the available range of the anode capacity can be reduced without lithium loss in the cathode active material due to pre-lithiated lithium, excessive volume change in silicon-based active materials can be suppressed, and the battery life characteristics can be improved. Furthermore, as a result, the capacity of the cathode active material can be utilized over its entire range, which has the advantage of increasing battery efficiency and maximizing energy density.

[0108] A positive electrode according to one embodiment of the present invention is characterized by not performing pre-lithiation by conventionally contacting a lithium metal layer with a negative electrode, but rather transferring and rolling a lithium metal layer onto the positive electrode, and then moving lithium ions inserted into the positive electrode to the negative electrode during the battery activation process.

[0109] An electrode according to one embodiment of the present invention may be an anode or a cathode, preferably a cathode, and more preferably a cathode in which a silicon-based active material is applied as a cathode active material, and specifically, the silicon-based active material may be silicon (Pure Si).

[0111] lithium secondary battery

[0112] The lithium secondary battery according to the present invention comprises a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the positive electrode or the negative electrode is manufactured by the method described above.

[0113] As the description regarding the anode and cathode above has been previously mentioned, it is omitted.

[0115] According to one embodiment of the present invention, the secondary battery includes a separator. The separator separates the negative electrode and the positive electrode and provides a pathway for the movement of lithium ions. Any separator commonly used as a separator in a secondary battery may be used without special limitations, and it is particularly desirable that it has low resistance to the movement of electrolyte ions and excellent electrolyte moisture retention capacity. Specifically, a porous polymer film, such as a porous polymer film made of a polyolefin-based polymer like an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, such as a nonwoven fabric made of high-melting-point glass fibers or polyethylene terephthalate fibers, may be used. Furthermore, a coated separator containing a ceramic component or a polymer material may be used to ensure heat resistance or mechanical strength, and may optionally be used in a single-layer or multi-layer structure.

[0117] According to one embodiment of the present invention, the secondary battery may further include an electrolyte. Examples of the electrolytes that can be used in the manufacture of lithium secondary batteries include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., but are not limited thereto.

[0118] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt. As the above-mentioned non-aqueous organic solvent, for example, aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyl lactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolone, formamide, dimethylformamide, dioxolone, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolone derivative, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivative, tetrahydrofuran derivative, ether, methyl propionate, ethyl propionate, etc. may be used.

[0119] In particular, among the above carbonate-based organic solvents, ethylene carbonate and propylene carbonate, which are cyclic carbonates, are high-viscosity organic solvents with high dielectric constants that effectively dissociate lithium salts, so they can be used preferably. Furthermore, if low-viscosity, low-dielectric constant linear carbonates such as dimethyl carbonate and diethyl carbonate are mixed with these cyclic carbonates in appropriate proportions, an electrolyte with high electrical conductivity can be produced, making it even more preferable to use.

[0120] The metal salt mentioned above may be a lithium salt, and the lithium salt is a substance that dissolves well in the non-aqueous electrolyte; for example, as the anion of the lithium salt, F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P- , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more types selected from the group consisting of can be used.

[0121] In addition to the above electrolyte components, the above electrolyte may further include one or more additives for the purpose of improving the lifespan characteristics of the battery, suppressing the decrease in battery capacity, and improving the discharge capacity of the battery, such as, for example, a haloalkylene carbonate-based compound such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride.

[0123] As described above, since the secondary battery including the positive electrode according to the present invention stably exhibits excellent capacity and capacity retention rate, it is useful in fields such as portable devices like mobile phones, laptop computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0124] Accordingly, according to another embodiment of the present invention, a battery module comprising the secondary battery as a unit cell and a battery pack comprising the same are provided.

[0125] The above battery module or battery pack can be used as a power source for one or more medium-to-large devices, including a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0127] Examples

[0128] Hereinafter, preferred embodiments are presented to aid in understanding the present invention; however, the above embodiments are merely illustrative of the description, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope and spirit of the description, and that such variations and modifications fall within the scope of the appended claims.

[0130] Electrode manufacturing

[0131] Example 1-1: Preparation of the cathode

[0132] Lithium metal was placed in a vacuum chamber so that both sides were exposed, and a lithium buffer layer with a thickness of 50 nm was formed on the surface by creating a mixed gas atmosphere of 95 vol% Ar and 25 vol% CO at room temperature (approx. 25°C). The lithium buffer layer was analyzed using X-ray photoelectron spectroscopy (XPS) (Nexsa ESCA System, Thermo Fisher Scientific (ESCA-02)) and confirmed that lithium carbonate was the main component, as it was found to be present in the form of 35 vol% Li, 25 vol% C, and 40 vol% O.

[0133] PET film (base film), a polymer layer (1 μm thickness) made of PMMA disposed on the PET film, and a lithium metal layer (6.2 μm thickness, 1.28 mAh / cm²) disposed on the polymer layer and made of solid lithium metal, with lithium buffer layers formed on both sides. 2 A transfer laminate containing a loading amount was prepared.

[0134] Meanwhile, average particle size D as the negative electrode active material 50 Silicon particles of 5 μm were used. A cathode was prepared comprising a pre-negative active material layer containing the above-mentioned cathode active material, carboxymethylcellulose (CMC) as a cathode binder, and carbon nanotubes as a cathode conductive material in a weight ratio of 80:10:10. The loading amount of the pre-negative active material layer was 10 mAh / cm² 2 It was, and the thickness was 75 μm.

[0135] The above transfer laminate is placed on a pre-negative active material layer to bring the lithium buffer layer and the pre-negative active material layer into contact, and then rolled using a roll press method, and aged for 120 minutes at room temperature in an atmosphere with 90 volume% nitrogen so that lithium is inserted into the negative active material layer.

[0137] Example 1-2: Preparation of the cathode

[0138] When preparing a transfer laminate, the lithium metal layer thickness is approximately 4 µm (0.82 mAh / cm²) 2 A pre-lithiated cathode was manufactured using the same method, except for the loading amount.

[0140] Examples 1-3: Preparation of the cathode

[0141] A pre-lithiated cathode was prepared using the same method, except that the thickness of the lithium buffer layer formed on both sides of the lithium metal layer was about 30 nm by controlling the time the lithium metal layer was exposed to a mixed gas atmosphere.

[0143] Comparative Example 1-1: Preparation of a cathode

[0144] A negative electrode was prepared in the same manner as in Example 1-1, except that a lithium metal layer without a lithium buffer layer was applied.

[0146] Comparative Example 1-2: Preparation of cathode

[0147] A cathode was prepared in the same manner as in Example 1-1, except that a lithium metal layer without a lithium buffer layer was applied and an air atmosphere (about 78 volume% nitrogen) was applied instead of a nitrogen atmosphere during aging.

[0149] Examples 1-4: Preparation of Anode

[0150] A transfer laminate was prepared in the same way as in Example 1-1 above.

[0151] Meanwhile, Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 was used. The above cathode active material is Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 Multiple primary particles (10 or more) combine with each other to form a secondary particle shape, and the average particle size D of the said secondary particles 50 The was 9㎛. A cathode was prepared comprising a pre-positive active material layer containing the above-mentioned cathode active material, PVdF as a cathode binder, and carbon nanotubes as a cathode conductive material in a weight ratio of 98:1:1, and an aluminum foil (thickness: 12㎛) as a cathode current collector. The loading amount of the pre-positive active material layer was 4.5mAh / cm² 2 It was, and the thickness was 140㎛.

[0152] The above transfer laminate is placed on a pre-negative active material layer to bring the lithium buffer layer and the pre-negative active material layer into contact, and then rolled using a roll press method, and aged for 120 minutes at room temperature in an atmosphere with 90 volume% nitrogen so that lithium is inserted into the positive active material layer.

[0154] Examples 1-5: Preparation of Anode

[0155] When preparing a transfer laminate, the lithium metal layer thickness is approximately 4 µm (0.82 mAh / cm²) 2 A pre-lithiated cathode was manufactured using the same method, except for the loading amount.

[0157] Examples 1-6: Preparation of Anode

[0158] A pre-lithiated cathode was prepared using the same method, except that the thickness of the lithium buffer layer formed on both sides of the lithium metal layer was about 30 nm by controlling the time the lithium metal layer was exposed to a mixed gas atmosphere.

[0160] Comparative Examples 1-3: Preparation of Anode

[0161] A positive electrode was manufactured in the same manner as in Example 1-2, except that a lithium metal layer without a lithium buffer layer was applied.

[0163] Comparative Examples 1-4: Preparation of Anode

[0164] A cathode was prepared in the same manner as in Examples 1-2, except that a lithium metal layer without a lithium buffer layer was applied and an air atmosphere (about 78 volume% nitrogen) was applied instead of a nitrogen atmosphere during aging.

[0166] Experimental Example 1: Evaluation of Pre-lithiation Reaction

[0167] For the pre-lithiation reactions of Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-4 above, the peak temperature of the reaction and the time for lithium nitride formation were measured and are shown in Table 1 below.

[0168] 1) Peak temperature (°C): The peak temperature is the highest reaction temperature recorded during the pre-lithiation reaction.

[0169] 2) Lithium nitride formation time (min): The lithium nitride formation time is the time recorded when the electrode surface begins to show a green light during the reaction, after performing a pre-lithiation reaction without removing the polymer layer (release layer) from the electrode structure. When lithium nitride is formed on the electrode surface, a green light appears due to the polymer layer on the surface. For electrodes whose surface color did not change to green during the pre-lithiation reaction, changes in the electrode state were observed for up to 7 days.

[0170] electrode Peak temperature (°C) Lithium nitride formation time Example 1-1 cathode 28 >120min Examples 1-2 cathode 27 >120min Examples 1-3 cathode 29 >120min Comparative Example 1-1 cathode 45 <10 min (Front) Comparative Example 1-2 cathode >60 <10 min (Front) Examples 1-4 anode 28 >120min Examples 1-5 anode 28 >120min Examples 1-6 anode 29 >120min Comparative Examples 1-3 anode 40 <10 min (Front) Comparative Examples 1-4 anode 52 <10 min (partial)

[0171] Referring to Table 1 above, in the case of the examples, lithium nitride was not formed during the reaction, and as a result of continuous storage and observation thereafter, it was confirmed that even after about 7 days, as shown in Fig. 5, no green light was observed and a purple light was displayed due to the surface polymer layer, indicating that the pre-lithiation reaction proceeded very stably within the room temperature range. However, in the case of Comparative Examples 1-1 and 1-3, it was confirmed that the peak temperature of the pre-lithiation reaction was relatively high because the lithium metal layer was not surface-treated, and it was observed that lithium nitride was formed 10 minutes after the start of the reaction, and through Fig. 6, it can be confirmed that green lithium nitride was formed on the entire surface of the electrode of Comparative Example 1-1.

[0172] In addition, Comparative Examples 1-2 and 1-4 are cases where pre-lithiation was carried out under normal atmospheric conditions without surface treatment. In Comparative Example 1-2, which is the cathode, the reaction was stopped when the reaction temperature exceeded 60°C due to the risk of explosion during the pre-lithiation reaction. In Comparative Example 1-4, the pre-lithiation reaction proceeded to a somewhat dangerous level, and the formation of lithium nitride was observed on a part of the electrode surface 10 minutes after the start of the reaction. As can be seen in Fig. 7, it can be seen that lithium nitride with a green tint was formed on a part of the surface.

[0174] Manufacturing of lithium secondary batteries

[0175] Examples 2-1 to 2-2 and Comparative Examples 2-1 to 2-2: Preparation of Lithium Secondary Batteries

[0176] Li[Ni as positive electrode active material 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 was used. The above cathode active material is Li[Ni 0.86 Co 0.05 Mn 0.08 Al 0.01 ]O2 Multiple primary particles (10 or more) combine with each other to form a secondary particle shape, and the average particle size D of the said secondary particles 50 The was 9㎛. A cathode was prepared comprising a cathode active material layer containing the above-mentioned cathode active material, PVdF as a cathode binder, and carbon nanotubes as a cathode conductive material in a weight ratio of 98:1:1, and an aluminum foil (thickness: 12㎛) as a cathode current collector. The loading amount of the above-mentioned cathode active material layer was 4.5mAh / cm² 2 It was, and the thickness was 140㎛.

[0177] The negative electrodes of Examples 1-1 and 1-2, Comparative Examples 1-1 and 1-2, the positive electrodes, and the porous polyethylene separator were assembled for each example and comparative example using a winding method, and an electrolyte (ethylene carbonate (EC) / ethylmethyl carbonate (EMC) = 3 / 7 (volume ratio)) and lithium hexafluorophosphate (LiPF6 1 mol) were injected into the assembled battery to produce a preliminary lithium-ion secondary battery.

[0178] The above-mentioned preliminary lithium-ion secondary battery was charged to 4.2V at a 0.1C C-rate, and then discharged to 2.5V to proceed with the activation process.

[0180] Examples 2-4 to 2-5 and Comparative Examples 2-3 to 2-4: Preparation of lithium secondary batteries

[0181] Average particle size D as cathode active material 50Silicon particles with a diameter of 5 μm were used. A cathode was prepared comprising a pre-negative active material layer containing the above-mentioned cathode active material, CMC as a cathode binder, and carbon nanotubes as a cathode conductive material in a weight ratio of 80:10:10. The loading amount of the pre-negative active material layer was 10 mAh / cm² 2 It was, and the thickness was 75 μm.

[0182] The positive electrode, the negative electrode, and the porous polyethylene separator of Examples 1-4, 1-5, Comparative Examples 1-3 and 1-4 were each assembled using a winding method for each example and comparative example, and an electrolyte (ethylene carbonate (EC) / ethylmethyl carbonate (EMC) = 3 / 7 (volume ratio)) and lithium hexafluorophosphate (LiPF6 1 mol) were injected into the assembled battery to manufacture a preliminary lithium-ion secondary battery.

[0183] The above-mentioned preliminary lithium-ion secondary battery was charged to 4.2V at a 0.1C C-rate, and then discharged to 2.5V to proceed with the activation process.

[0185] Experimental Example 2: Evaluation of Resistance and Lifetime Characteristics

[0186] Charge and discharge were performed on each of the lithium secondary batteries of Examples 2-1, 2-2, 2-4 and 2-5 and Comparative Examples 2-1 to 2-4, and resistance characteristics and lifespan characteristics were evaluated by the following method, and the results are shown in Table 2 below.

[0187] 1) Resistance characteristics: The resistance was measured by applying a 2.5C pulse current for a specific time at 50% SOC during discharge per cycle while running charge-discharge cycles on the above lithium secondary battery under the following conditions.

[0188] Resistance increase rate: [(Resistance value after 200 cycles) / (Resistance value at 1 cycle)] x 100

[0189] 2) Life characteristics: The first and second cycles were charged and discharged at 0.1C, and from the third cycle onwards, the cycles were run with 1C charging and 0.5C discharging, and the number of cycles in which the SOC was maintained at 80% or higher was measured.

[0190] Charging conditions: CC (Constant Current) / CV (Constant Voltage) (5mV / 0.005C current cut-off) 4.2V

[0191] Discharge condition: CC (constant current) condition 2.5V

[0193] Resistance (mΩ) Number of cycles to maintain SOC at 80% 1 time 50 times 100 times 150 times 200 times Resistance increase rate (%) cathode Example 2-1 0.88 0.88 0.95 1.05 1.23 139% 200 Example 2-2 0.88 0.89 0.85 1.01 1.28 145% 200 Comparative Example 2-1 1.47 1.87 2.10 2.15 2.33 158% 30 Comparative Example 2-2 1.25 1.24 1.41 1.87 2.09 167% 50 anode Examples 2-4 0.87 0.87 0.88 0.90 1.01 116% 350 Examples 2-5 0.93 0.92 0.93 1.00 1.11 119% 250 Comparative Example 2-3 0.98 1.10 1.17 1.25 1.48 151% 250 Comparative Example 2-4 0.98 1.01 1.08 1.19 1.52 155% 150

[0194] Referring to Table 2 above, it can be confirmed that the lithium secondary batteries of Examples 2-1 and 2-2, equipped with a negative electrode to which the pre-lithiation method according to the present invention is applied, have excellent resistance characteristics, with lower initial resistance and lower resistance growth rate compared to the lithium secondary batteries of Comparative Examples 2-1 and 2-2, equipped with a negative electrode not to which the method is applied. This is understood to be because lithium nitride is formed on the surface and acts as a resistor, and it can be seen that it continues to act as a resistor without decomposing even during the cycling process.

[0195] It can be confirmed through a comparison of Examples 2-4 and 2-5 and Comparative Examples 2-3 and 2-4 that the same applies to the anode. In particular, in the case of the anode, there was no extreme difference in the initial resistance value as with the cathode, but it can be confirmed that the resistance increased significantly in the case of the comparative example.

[0196] Meanwhile, regarding the lifespan characteristics, when comparing Examples 2-1 and 2-2 with Comparative Examples 2-1 and 2-2, it can be seen that the effect is maximized when the method of the present invention is applied to the cathode, and even when comparing Examples 2-4 and 2-5, which are the anodes, with Comparative Examples 2-3 and 2-4, it can be confirmed that there is a clear improvement, although not as significant a difference as with the cathode. Explanation of the symbols

[0198] 110: Electrode current collector 120, 120`: Preliminary electrode active material layer 300: Transfer laminate 310: Base film 320: Lithium metal layer 321: Lithium buffer layer 330: Polymer layer 400: Electrode structure R: LoL

Claims

Claim 1 A method for manufacturing an electrode, comprising: a step P1 of forming an electrode structure by placing a transfer laminate including a lithium metal layer having lithium buffer layers formed on both sides onto a pre-electrode active material layer so that the lithium buffer layer and the pre-electrode active material layer come into contact; a step P2 of rolling the electrode structure; and a step P3 of aging the rolled electrode structure in a nitrogen atmosphere; wherein the nitrogen atmosphere is an atmosphere containing 80 volume% or more of nitrogen, and the lithium buffer layer does not contain lithium nitride. Claim 2 A method for manufacturing an electrode according to claim 1, wherein the aging of the P3 step is performed at 15°C to 40°C. Claim 3 A method for manufacturing an electrode according to claim 1, wherein the lithium buffer layer comprises lithium carbonate. Claim 4 A method for manufacturing an electrode according to claim 3, wherein the lithium buffer layer further comprises one or more of lithium oxide and lithium hydroxide. Claim 5 delete Claim 6 A method for manufacturing an electrode according to claim 1, wherein the thickness of the lithium metal layer is 1 μm to 10 μm. Claim 7 A method for manufacturing an electrode according to claim 1, wherein the thickness of the lithium buffer layer is 50 nm or less. Claim 8 A method for manufacturing an electrode according to claim 1, wherein the transfer laminate is manufactured by a method comprising the step (S1) of surface treating both sides of a lithium metal layer under a mixed gas atmosphere of CO2 and Ar to form a lithium buffer layer. Claim 9 A method for manufacturing an electrode according to claim 1, wherein the electrode is a negative electrode and the electrode active material is a negative electrode active material comprising a silicon-based negative electrode active material. Claim 10 An electrode comprising: a current collector; an electrode active material layer disposed on the current collector; and a lithium buffer layer disposed on the electrode active material layer; wherein the lithium buffer layer comprises one or more of lithium carbonate, lithium oxide, and lithium hydroxide, and is an electrode not containing lithium nitride, wherein the electrode comprises a transfer laminate including a lithium metal layer having a lithium buffer layer formed on both sides; and a pre-electrode including a current collector and a pre-electrode active material layer disposed on the current collector; and wherein the lithium buffer layer of the transfer laminate and the pre-electrode active material layer of the pre-electrode are disposed in contact with each other. Claim 11 delete Claim 12 The electrode of claim 10, wherein the electrode is a negative electrode and the electrode active material is a negative electrode active material comprising a silicon-based negative electrode active material. Claim 13 A lithium secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the positive electrode or the negative electrode is the electrode of claim 10.

Citation Information

Patent Citations

  • Electrode protective structure

    JP2016512380A

  • Method for manufacturing negative electrode with inorganic coating layer

    KR1020220051500A

  • Negative electrode and method of pre-lithiating a negative electrode

    KR1020220061641A

  • Method of pre-lithiating an anode for lithium secondary battery and Lithium metal laminate for being used therefor

    KR1020190083305A